Hyperprolactinaemia and its Comparision with Hypothyroidism in Primary Infertile Women - Turankar, Sunita (JCDR Research and Publications (P) Limited, 2013)
Aim and Objective: To study the serum prolactin levels and the serum TSH in primary infertile females. Material and Method: In this study, we investigated thirty women who were diagnosed cases of primary infertility, who attended the Biochemistry Department, Sir JJ Group of Hospitals, Mumbai, India, for hormonal evaluations. Thirty fertile women with similar ages were enrolled as the controls. The status of the thyroid dysfunction and the levels of serum prolactin were reviewed in infertile women and in the controls. The serum Prolactin and the thyroid stimulating hormone levels were measured by using Siemens kits in IMMULITE 1000 chemiluminescence immunoassays. Results: In our study, the serum prolactin levels in the infertile group were found to be high as compared to those in the control group and they were highly significant (p<0.0001). The serum TSH levels in the infertile group were found to be high, as compared to those of control group and they were highly significant (p<0.0001). Conclusion: There is a higher incidence of hyperprolactinaemia in infertile patients. There is also a greater propensity for thyroid disorders in infertile women than in the fertile ones. The incidence of hypothyroidism in the hyperprolactinaemic subjects in the study population was found to be highly significant than the normal controls.